A systematic review of the benefits of mindfulness‐based interventions following transient ischemic attack and stroke. Issue 6 (23rd July 2013) - Lawrence, Maggie; Booth, Jo; Mercer, Stewart; Crawford, Elizabeth
<x xml:space="preserve">Abstract</x> Background Recent epidemiological studies have demonstrated an association between perceived psychological stress and ischemic stroke. A feature of stroke is recurrence; 30–40% within five‐years following first transient ischemic attack/stroke. Equipping patients with skills and coping strategies to help reduce or manage perceived psychological stress may represent an important secondary prevention intervention. Mindfulness‐based interventions are structured, group‐based self‐management programmes with potential to help people with long‐term conditions cope better with physical, psychological, or emotional distress. Review evidence suggests significant benefits across a range of physical and mental health problems. However, we could find no evidence synthesis relating specifically to the benefits of mindfulness‐based interventions following transient ischemic attack/stroke. Aim The review aims to evaluate the benefits of mindfulness‐based interventions following transient ischemic attack/stroke. Methods Six major databases were searched using subject headings and key words. Papers were screened using review‐specific criteria. Critical appraisal and data extraction were conducted independently by two reviewers. Statistical meta‐analysis was not possible; therefore findings are presented in narrative form. Results Four studies involving 160 participants were reviewed. Three papers reported mindfulness‐based interventions delivered to groups; one paper reported a mindfulness‐based intervention which was delivered one to one. The results demonstrate a positive trend in favor of the benefits of mindfulness‐based interventions across a range of psychological, physiological, and psychosocial outcomes including anxiety, depression, mental fatigue, blood pressure, perceived health, and quality of life. No evidence of harm was found. Conclusion Following transient ischemic attack/stroke, people may derive a range of benefits from mindfulness‐based interventions; however, further methodologically robust trials are required.